MEMBANGUN MODEL KERJASAMA PENGELOLAAN PERBATASAN NEGARA DI KALIMANTAN BARAT-SARAWAK (Suatu Studi Perbandingan) - Budi Hermawan Bangun (Masalah-Masalah Hukum, 2014)
State's border management cooperation between Indonesia and Malaysia keep potential problems namely differences in socio-economic conditions between the two states. Meanwhile as a socio-cultural, the communities in the two states have a close relationship. Support by comparative study, this paper want to recomended a model of state's border management cooperation, particularly between West Kalimantan and Sarawak. From the results of the comparative study it was concluded that adoption of the China-Vietnam border management model can be applied to the Indonesia-Malaysia border management, in particular between West Kalimantan-Sarawak. This adoption should be accompanied by a number of strategies, i.e.: accelerating the construction of the infrastructure and facilities, strengthening the socio-economic conditions, human resources development, and strengthening the aspect of good institutional